POLA MODUS OPERANDI FRAUD PEMBIAYAAN SERTA UPAYA MEMINIMALISIR KECURANGAN PADA BANK PERKREDITAN RAKYAT SYARIAH X - Purwanto, Purwanto; Kusuma, Andriani (JURNAL AKUNTANSI DAN INVESTASI, 2019)
The purpose of this study is to examine and explain the operandi pattern of fraud that occurs in the distribution of bank financing and explain the efforts to minimize fraud that occurs in the distribution of bank financing. The results of the study show that. This research is a type of qualitative research with the research design used is a case study in BPRS X. The data in this study consisted of documentation, interviews, and observations. The results showed that there were elements of BPRS X who had practiced fraud starting from the submission stage, data analysis and approval in the form of falsifying documents by conditioning the submission so that they could pass the financing so that there were mask credit findings, credit in the name. As well as efforts to minimize fraud consisting of Pillar steps to prevent, detect, investigate and monitor and evaluate existing systems.